2004
DOI: 10.1095/biolreprod.104.031252
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Survival Versus Degradation in the Mammalian Epididymis: A Hypothesis1

Abstract: A long-standing problem in epididymal physiology is the fate of unejaculated spermatozoa in the cauda epididymidis under conditions such as congenital absence of the vas deferens, long-term vasectomy, or castration. There is no convincing evidence for significant absorption of spermatozoa, defective or otherwise, by spermiophagy or dissolution in the epididymis of normal animals. Spermiophagy by epithelial cells or intraluminal macrophages may take place if the duct ruptures and granulomas form (e.g., after ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
79
0
7

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 58 publications
9
79
0
7
Order By: Relevance
“…According to Plant and Marshall (2001), high intratesticular testosterone concentration is required for the regulation of spermatogenesis, the reduction of which results in fewer matured sperm produced by the testis. Furthermore, the reduced concentrations of plasma testosterone among BaP-exposed rats compared with UNC may have caused a rapid regression in the epididymal epithelium, especially in the initial segment and the proximal caput epididymal region (Jones, 2004). As a result, epididymal sperm maturation and survival were adversely affected and during the ensuing weeks, only a few degenerated sperm became present in the cauda epididymides and vas deferens (Jones, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Plant and Marshall (2001), high intratesticular testosterone concentration is required for the regulation of spermatogenesis, the reduction of which results in fewer matured sperm produced by the testis. Furthermore, the reduced concentrations of plasma testosterone among BaP-exposed rats compared with UNC may have caused a rapid regression in the epididymal epithelium, especially in the initial segment and the proximal caput epididymal region (Jones, 2004). As a result, epididymal sperm maturation and survival were adversely affected and during the ensuing weeks, only a few degenerated sperm became present in the cauda epididymides and vas deferens (Jones, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reduced concentrations of plasma testosterone among BaP-exposed rats compared with UNC may have caused a rapid regression in the epididymal epithelium, especially in the initial segment and the proximal caput epididymal region (Jones, 2004). As a result, epididymal sperm maturation and survival were adversely affected and during the ensuing weeks, only a few degenerated sperm became present in the cauda epididymides and vas deferens (Jones, 2004). Raychoudhury and Kubinski (2003) reported that in vitro exposure of isolated rat Sertoli cells to BaP resulted in cellular changes characteristic of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been recently shown that estrogens may be functionally indispensable for epididymal function [McCarthy et al 2006], it is known that epididymal functions in the majority of mammals, including epididymal sperm transport, sperm maturation and sperm storage, heavily depend on testicular androgen secretion [Holland et al 1992;Orgebin-Crist 1996;Moore and Akhondi 1996]. When, in otherwise intact animals, the cauda epididymis is physiologically isolated in situ by ligation of both of its extremes, the stored spermatozoa degenerate within several weeks but do not decrease noticeably in number [Lubicz-Nawrocki 1976;Jones 2004]. However, when subject to bilateral orchidectomy at the same time that the cauda epididymis is isolated, spermatozoa rapidly die and practically disappear (490%) in a few days.…”
mentioning
confidence: 99%